Strategi Pembelajaran Siswa Dengan Gangguan Pemusatan Perhatian dan Hiperaktivitas di Kelas Inklusi - M Kusuma Wardhani (JURNAL ARMADA PENDIDIKAN, 2026)
Inclusive education requires teachers to respond to diverse student characteristics, including those with Attention Deficit Hyperactivity Disorder (ADHD). In practice, however, pedagogical responses to students with ADHD often focus primarily on controlling observable behavior without addressing underlying cognitive and emotional regulation needs. This article aims to synthesize evidence-based instructional strategies that support students with ADHD in inclusive classrooms. A literature review approach was employed by examining scholarly publications from 2000–2024 related to instructional strategies and classroom management for students with ADHD. The data were analyzed thematically to identify consistent patterns across studies. The findings indicate that effective strategies include environmental modification, simplified instructions, active and varied learning activities, positive reinforcement systems, short and structured learning sessions, and collaboration between teachers and parents. These strategies are most effective when implemented as responses to students’ self-regulation needs rather than merely behavioral control measures. This review highlights the importance of strengthening teachers’ understanding of the neurodevelopmental dimensions of ADHD to foster more adaptive and supportive inclusive learning environments.